Deep brain stimulation of the ventralis oralis anterior thalamic nucleus is effective for dystonic tremor. (December 2020) - Mongardi, L.; Rispoli, V.; Scerrati, A.; Giordano, F.; Capone, J.G.; Vaudano, A.E.; De Bonis, P.; Morgante, F.; Picillo, M.; Cavallo, M.A.; Sensi, M.
Highlights: VoA – DBS is effective on both dystonia and tremor. VoA – DBS benefits are not impaired by tolerance or side effects. The variable VoA-DBS outcome previously reported were not proven by VTA simulation. Application of new consensus on tremor classification may improve patient selection.